Multilayer circuits with thick-film polymer insulation - Spirin, V. G. (Technology and design in electronic equipment, 2012)
Three design and technological versions of multilayer circuit have been developed. The interlayer and protective isolation in these circuits was performed with thick (10–30 micron) heat-resistant photosensitive organic dielectric film. Such performance allows attaching component leads to the contact pads on the interlayer isolation with the use of ultrasonic welding and soldering. Number of interlayer connections of conductors in such circuits is minimized. The complexity and cost of manufacturing of the circuits can be reduced by 2–3 times compared to known thin-film prototypes.